Characteristics of Nails with Lichen Planus (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
The study revealed that the most common nail lesions in lichen planus are longitudinal grooves, general dystrophic changes in the nails in the form of fragility, onychorrhexis and trachyonychia. It was also noted that lichen planus is characterized by severe irreversible changes in the nails, such as anonychia and pterygium. In the course of this work, we noted the evolution of pathological changes in the nails in lichen planus. This observation can be useful in the diagnostic search and choice of treatment tactics in the early stages of the lesion.